Genetic progress in grain yield radiation and nitrogen use efficiency of dryland winter wheat in Southwest China since 1965: Progress and prospect for improvements. Issue 6 (19th September 2021) - Yang, Hongkun; Mo, Piao; Chen, Yufeng; Chen, Renhua; Wei, Ting; Xie, Wei; Xiang, Xiaolin; Huang, Xiulan; Zheng, Ting; Fan, Gaoqiong
Abstract: Investigations of critical physiological traits associated with the genetic yield gain in wheat ( Triticum aestivum ) are essential to determine future crop breeding and management strategies. This study grew 32 cultivars released from 1965 to 2017 for two cropping seasons (a dry year, 2016–2017, and a humid year, 2017–2018) to examine yield potential achieved through efficiencies in canopy light interception, solar energy conversion, harvest index (HI), and nitrogen (N) uptake and utilization. Yield gain for wheat (25.0 ± 1.8 kg ha −1 yr −1 ) resulted from increases in plant biomass, HI, and N utilization efficiency (NUtE). Modern cultivars with an erect canopy and slender flag‐leaves optimized light interception and could achieve higher biomass yield. The introduction of semi‐dwarf genes ( Rht‐8 ) reduced plant height (0.05 yr −1 ) and improved HI (0.004 yr −1 ) and NUtE resulting from both increased pre‐anthesis accumulated biomass and plant dry matter mobilization after anthesis. Greater biomass partitioning to spikes resulted in higher fruiting efficiency and grain number. Due to greater tillering capability through increased N uptake efficiency, increased fertile spikes and grain yield were observed. Among these newer cultivars, the rate of yield gain was slow, and yield stability was more affected by accumulative rainfall than diurnal temperature. The future challenge of wheat breeding is to maintain the genetic yield gain without increasing the reliance on chemical fertilizers under an increasingly variable climate. Core Ideas: Yield gain for wheat from 1965 to 2017 resulted from increases in plant biomass, HI, and N utilization efficiency (NUtE). Random forests model predicts environmental factor effects on yield components. Greater biomass partitioning to spikes resulted in high fruiting efficiency and grain number. Genetic gain in NUtE helped achieve target yield and reduced reliance on chemical fertilizer.